Promoting urban regeneration and aging in place: APRAM – An interdisciplinary method to support decision-making in building renovation - Serrano-Jiménez, A.; Lima, M. L.; Molina-Huelva, M.; Barrios-Padura, A. (Sustainable Cities and Society, 2019)
Current European policies aim to promote the sustainable urban regeneration of housing stock while ensuring aging in place. Following these targets, this research proposes the Architectural and Psycho-environmental Retrofitting Assessment Method (APRAM) as an interdisciplinary decision support system, specifically designed to be applied in building renovation, which considers architectural demands and residents’ perceptions. This method generates an integral diagnosis that combines an architectural evaluation, through technical inspection grids, and psycho-environmental perceptions, by gathering residents’ responses from a participatory survey, in order to facilitate decision-making regarding renovation proposals. Retrofitting interventions, structured in public space, building, and dwelling scales, are assessed using architectural priority levels as well as social and engagement indicators of satisfaction, attachment, social need, and willingness to participate, thereby establishing a decision support system for property owners or public entities. APRAM is applied and tested in a residential neighbourhood of Lisbon (Portugal), for which its architectural, social and economic reports are defined in a summary table and a graphical display that show the integral performance of each intervention. Over 80% of responses involve major demands for which the proposed method shows close connections between the architectural diagnosis and residents’ perceptions for the decision-making process.